Smoking as A Risk Factor for Periodontitis in Erbil City - Saya Mustafa Azeez (Eurasian Journal of Science and Engineering, 2023)
Background and Objective: Nicotine in cigarettes can harm the immune system and lead to constriction of blood vessels, plus the blood vessels in the tissues encircling the tooth. Constriction of blood vessels can form an encouraging environment for the growth of microorganisms that cause periodontal disease. The purpose of this study is to verify the risk of smoking on the periodontal health status. Material and Method: a comparative cross-sectional study carried out on 400 patients including 200 smokers and 200 nonsmokers of age range (18-64) years. Chi-square test was used to compare data recorded (p-value <0.05). Results: Most of the smokers were male. Most of the participants didn’t use interdental aid. There was a significant relation between age, gender, smoking habit including frequency and duration, oral hygiene habit, and dental care visit with periodontitis (P-value <0.05). Conclusion: The current study demonstrates smoking as the major etiological factor associated with periodontal tissue destruction.